Studies of Spectral and Magnetic Behaviour of Some Complexes of Co(II), Ni(II) and Cu(II) Ions with 2-(Acetylacetonato) Imino Aceto Hydroxamine Acid - Tahkur, S.N.; Brat Singh, Shiv; Kumar, Sanjay; Singh, S.P.; Kumari, Anupama (Asian Journal of Chemistry, 2010)
A series of complexes of the type MLB3 [M = Co(II), Ni(II) and Cu(II) ions, B = H2O, pyridine and γ-picoline] have been synthesised with hydroxamic acid as ligand, H2L. Characterisation of the ligand and the complexes has been done on the basis of elemental analysis, spectral stqdies, magnetic susceptibility and electrical conductivity measurements. The ligand has been found to coordinate through two nitrogen and one oxygen atoms. Since the complexes are found to be octahedral, the remaining three coordination sites are satisfied by oxygen of H2O and nitrogen donor molecules such as pyridine and γ-picoline.